Incidence of university management on student dropout in public universities in Chile - Sanhueza Gutiérrez, Daniela; King-Domínguez, Andrea; Amestica-Rivas, Luis (IE Revista de Investigación Educativa de la REDIECH, 2021)
Student dropout affects education systems globally and Chile is no exception, especially in the university sector. There is no single reason that leads students to drop out, but rather it is a multicausal phenomenon, conditions of each institution take relevance when trying to explain this phenomenon. In this context, the objective of this research is to identify and analyze the institutional factors that explain student dropout in Chilean universities. Starting from a sample of 28 so-called public universities, integrated by private and state institutions, three types of panel-type regressions of data on explanatory variables were applied for the period 2016-2018. In a first analysis, it was evidenced that the average student dropout rate is higher in state universities compared to private ones. Similarly, it was found that the greater the number of teachers with postgraduate degrees, the greater the number of square meters of study rooms, laboratories, and classrooms per student, and the greater the number of academic libraries, the lower the student dropout rate. These results could be interesting for the definition of institutional policies.